Development of therapeutic PD-1 monoclonal antibodies for treatment of canine tumor - Jinquan He; Xuan Yin; Anqi Xie; Ning Wang; Zeming Guo; Yizhou Chen; Weidong Cui; Xueqiao Qian; Chungen Pan (Veterinary Immunology and Immunopathology, 2026)

A metabolism-driven multifunctional hydrogel promotes adipocyte differentiation and reduces fibrotic skin repair - Zhangrui Wu; Liping Zhang; Yi Wang; Zixuan Feng; Zeming Zhuang; Xincao Zhong; Chunye Chen; Xiaoying Lin; Yong Wang; Xuewen Wang; Kai Guo; Jun Chen; et al. (Chemical Engineering Journal, 2026)

Discovery of Meso- to Neoproterozoic magmatism and metamorphism in the eastern Himalaya: Implications for assembly of the Rodinia supercontinent - Chengyuan Zhang; Zeming Zhang; Richard M. Palin; Xin Dong; Mingming Guo; Shuangpeng Wu; Yanfei Chen; Jin Luan (Precambrian Research, 2026)

Linearized dynamic modeling and pose prediction of AUV based on an improved EDMD framework - Qianqi Liu; Kuo Chen; Zhier Chen; Kai Ren; Zeming Wu; Jiancheng Yu (Ocean Engineering, 2026)

Non-additive effects of microplastics, atrazine, and sulfamethoxazole co-exposure on Penaeus vannamei health and environmental risks - Yinan Wang; Qiangqiang Shi; Weijia Gan; Feng Xu; Hao Liu; Liuquan Zhang; Rongrong Zhang; Jiong Chen; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2026)

Performance study on a cryogenic bubble pump for low-flow-rate liquid nitrogen transfer - Yuhui Chen; Ya Xu; Daming Sun; Zeming Wang; Qie Shen (International Journal of Refrigeration, 2026)

17β-estradiol-induced growth–defense tradeoffs in pak choi (Brassica) and implications for intake risk - Yang Chen; Junyue Wang; Zikang Zhang; Zeming Wang; Youai Zhang; Yanzheng Gao; Chao Qin; Wanting Ling (Journal of Environmental Management, 2026)

Corrigendum to “Microstructure characteristics and corrosion behaviors of Mg alloys under various multiple-passes hot-rolling deformation” [Chem. Eng. J. 524 (2025) 169715] - Yuan Zhang; Zeming Li; Wei Liu; Yun Liu; Liansheng Chen (Chemical Engineering Journal, 2026)

Analysis of the fire evolution process of an electric vehicle in a confined garage - Liang Yin; Ruichao Wei; Liang Zhang; Shaozhang Chen; Zeming Ren; Zongcun Wang; Shenshi Huang (Tunnelling and Underground Space Technology, 2026)

Pathogen-induced H2O2 triggers phosphorylation of the RNA-binding protein RRM2R to suppress OsMAPKKK18 intron retention for orchestrating rice immunity and growth - Xiang Lu; Yibang An; Wenxiu Lu; Jing Li; Qing Xiong; Miaomiao Zhu; Yao He; Jia Yang; Yue Wang; Zeming Zhang; Xiaorong Gong; Yulong Qian; et al. (Molecular Plant, 2026)

Towards coordinated sustainability: A systematic study of cross-regional synergy in pollution reduction and CO2 mitigation in the Dongjiang River Basin - Yongxi Sun; Yulei Xie; Jinhui Hu; Qitao Rao; Zeming Chen (Journal of Environmental Management, 2025)

Microstructure characteristics and corrosion behaviors of Mg alloys under various multiple-passes hot-rolling deformation - Yuan Zhang; Zeming Li; Wei Liu; Yun Liu; Liansheng Chen (Chemical Engineering Journal, 2025)

A durable immuno-protective core-shell microgel for the enhanced pancreatic islet transplantation in diabetes therapy - Zeming Hu; Yang Luo; Muhammad Junaid; Rong Xu; Yaoqi Chen; Jie Yao; Renhao Ni; Tong Zhu; Hua Zhang; Huiqing Ding; Yabin Zhu (Chemical Engineering Journal, 2025)

ET-PatchNet: A low-memory, efficient model for Multi-view Stereo with a case study on the 3D reconstruction of fruit tree branches - Hao Wan; Xilei Zeng; Zeming Fan; Qinhu Chen; Ke Zhang; Han Zhang (Computers and Electronics in Agriculture, 2025)

Heteroaggregation between polystyrene micro(nano)plastics and dibutyl phthalate mediates toxicity reduction in macroalgae: Physiological and transcriptomic evidence from Gracilariopsis lemaneiformis - Yuanxia Li; Xiaoqian Zhang; Nianjun Xu; Mingze Chen; Wenting Tang; Na Zhou; Ting Zeng; Xue Sun; Zeming Zhang (Journal of Hazardous Materials, 2025)

Extremely high toxicity of gaseous intermediate/semi volatile organic compounds emitted from typical incomplete biomass burning in China - Yueqian Wang; Di Wu; Zihua Guo; Xiu Chen; Yang Li; Yifei Tan; Zeming Ye; Yuzhe Liu; Yaoqiang Huo; Qing Li; Jianmin Chen (Journal of Hazardous Materials, 2025)

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

Controlled-release oxidants for in situ remediation of organic contaminated soil and groundwater: Material preparation, mechanisms, and applications - Jia Shen; Zili Jiang; Hongyun Shao; Zeming Xie; Yue Han; Jia Liu; Hongxin Chen; Shijin Feng; Yang Liu; Xiuxiu Ruan (Journal of Hazardous Materials, 2025)

Critical control points in Penaeus vannamei aquaculture: Dynamic tracking and comprehensive risk assessment of antibiotics - Feng Xu; Chenxue Yang; Hua Liu; Hao Liu; Mingze Chen; Yinliang Wu; Xizhi Shi; Zeming Zhang; Rongrong Zhang (Journal of Hazardous Materials, 2025)

Identification of Mitochondrial and Succinylation Modification-Related Gene Signature in Ischemic Stroke - Lixia Wang; Jishuai Zhao; Hui Cai; Xiaoling Ying; Yonglei Liu; Zeming Luo; Heyan Chen; Lin Yang (Molecular Neurobiology, 2025)

The crustal structure of southeast Tibet from joint inversion of surface wave dispersion and gravity anomaly data - Haopeng Chen; Ruirui Fan; Nanqiao Du; Feng Bao; Zeming Zhang; Xuelei Li; Fang Zou; Chuang Xu (Journal of Asian Earth Sciences, 2024)

Corrigendum to “Platelet membrane fusion liposome loaded with type I AIE photosensitizer to induce chemoresistance cancer pyroptosis and immunogenic cell death for enhancing cancer immunotherapy” [Chem. Eng. J. 476 (2023) 146276] - Hao Chen; Xi Luo; Qinghua Huang; Zeming Liu; Meng Lyu; Dexin Chen; Jianlan Mo; Daoming Zhu (Chemical Engineering Journal, 2024)

Endowing polymeric carbon nitride photocatalyst with CO2 activation sites by anchoring atomic cobalt cluster - Yaru Shang; Yijie Hou; Xun Cao; Hengjie Liu; Xiaoli Jin; Jiawei Liu; Chunshuang Yan; Yumin Qian; Li Song; Zeming Qi; Pin Song; Yansong Zhou; et al. (Chemical Engineering Journal, 2024)

A RRT based path planning scheme for multi-DOF robots in unstructured environments - Meilin Kang; Qinhu Chen; Zeming Fan; Chuan Yu; Yixin Wang; Xiaojun Yu (Computers and Electronics in Agriculture, 2024)

Improvement of rat hepatocellular carcinoma model induced by diethylnitrosamine - Runzhui Lin; Sitian Xie; Fengjie Xu; Zeming Chen; Jianrui Liu; Xingmu Liu (Tissue and Cell, 2024)

Microphysical and dynamic evolution of convection observed by polarimetric radar under the influence of cloud seeding - Hepeng Zheng; Yun Zhang; Yichen Chen; Deping Ding; Zuhang Wu; Mengyu Huang; Hui He; Xincheng Ma; Zeming Zhou (Atmospheric Research, 2024)

Combined effects of microplastics and antibiotic-resistant bacteria on Daphnia magna growth and expression of functional genes - Xiaofeng Chen; Xiaocui Wang; Yuanyin Huang; Ziying Zhu; Tianmu Li; Zeming Cai; Minqian Li; Han Gong; Muting Yan (Science of The Total Environment, 2023)

Origin, formation, and transformation of different forms of silica in Xuanwei Formation coal, China, and its’ emerging environmental problem - Zailin Chen; Zeming Shi; Shijun Ni; Bangzheng Ren; Junchun Hu (Environmental Science and Pollution Research, 2023)

Platelet membrane fusion liposome loaded with type I AIE photosensitizer to induce chemoresistance cancer pyroptosis and immunogenic cell death for enhancing cancer immunotherapy - Hao Chen; Xi Luo; Qinghua Huang; Zeming Liu; Meng Lyu; Dexin Chen; Jianlan Mo; Daoming Zhu (Chemical Engineering Journal, 2023)

Quantitative evaluation on phosphate adsorption by modified biochar: A meta-analysis - Zeming Xu; Changhui Zhang; Chunhong Zhang; Zhe Chen (Process Safety and Environmental Protection, 2023)

Implanting nitrogen-doped graphene quantum dots on porous ultrathin carbon nitride for efficient metal-free photocatalytic hydrogen evolution - Hanxiang Chen; Zhao Mo; Zeming Wang; Pengcheng Yan; Peipei Sun; Guanyu Wu; Jinyuan Zhang; Xianglin Zhu; Liang Wang; Hui Xu (Journal of Environmental Chemical Engineering, 2023)

Environmental profile, potential sources, and ecological risk of polycyclic aromatic hydrocarbons in a typical coastal bay and outer bay area - Yuyao Wu; Zeming Zhang; Wei Huang; Hua Liu; Rongrong Zhang; Haifeng Jiao; Aili Sun; Jiong Chen; Xizhi Shi (Environmental Science and Pollution Research, 2023)

Microplastic pollution and enrichment of distinct microbiota in sediment of mangrove in Zhujiang River estuary, China - Muting Yan; Xiaofeng Chen; Wei Chu; Weixin Li; Minqian Li; Zeming Cai; Han Gong (Journal of Oceanology and Limnology, 2023)

Ships’ Small Target Detection Based on the CBAM-YOLOX Algorithm - Yuchao Wang; Jingdong Li; Zeming Chen; Chenglong Wang (Journal of Marine Science and Engineering, 2022)
In order to solve the problem of low accuracy of small target detection in traditional target detection algorithms, the YOLOX algorithm combined with Convolutional Block Attention Module (CBAM) is proposed. The algorithm first uses CBAM on the shallow feature map to better focus on small target information, and the Focal loss function is used to regress the confidence of the target to overcome the positive and negative sample imbalance problem of the one-stage target detection algorithm. Finally, the Soft Non-Maximum Suppression (SNMS) algorithm is used for post-processing to solve the problem of missed detection in close range ship target detection. The experimental results show that the average accuracy of the proposed CBAM-YOLOX network target detection is improved by 4.01% and the recall rate is improved by 8.81% compared with the traditional YOLOX network, which verifies the effectiveness of the proposed algorithm.

Intravenous immunoglobulin is effective in alleviating hepatic ischemia–reperfusion injury: a rat model study - Zeming Chen; Runzhui Lin; Hua Zhuo; Fengjie Xu; Xingmu Liu (Molecular Biology Reports, 2022)

Early Mesozoic magmatism and tectonic evolution of east-central Tibet - Yanfei Chen; Zeming Zhang; Zuolin Tian; Xin Dong; Huixia Ding; Hongchen Mu; Dongyan Kang; Yunshuai Li (International Journal of Earth Sciences, 2018)

Single crystal growth, characterization and high-pressure Raman spectroscopy of impurity-free magnesite (MgCO3) - Wen Liang; Zeming Li; Yuan Yin; Rui Li; Lin Chen; Yu He; Haini Dong; Lidong Dai; Heping Li (Physics and Chemistry of Minerals, 2018)